1994
DOI: 10.1111/j.1365-2826.1994.tb00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Steroid Receptors: Interactions with Brain Neuropeptide Systems in Relation to Nutrient Intake and Metabolism

Abstract: The glucocorticoid, corticosterone (CORT), is believed to have an important function in modulating nutrient ingestion and metabolism. Recent evidence described in this review suggests that the effects of this adrenal hormone are mediated through two steroid receptor subtypes, the type I mineralocorticoid receptor and the type II glucocorticoid receptor. These receptors, which have different affinities for CORT, respond to different levels of circulating hormone. They mediate distinct effects of the steroid, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
127
0
6

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(142 citation statements)
references
References 259 publications
(448 reference statements)
9
127
0
6
Order By: Relevance
“…mRNA expressions of NPY, proopiomelanocortin (POMC) and cocaine-amphetamine regulated transcript (CART) in the arcuate nucleus responding to food deprivation were examined together with the plasma levels of leptin and corticosterone. Circulating leptin decreases (Schwartz et al, 1995;Ahima et al, 1996;Makimura et al, 2003) and corticosterone increases (Timofeeva et al, 2002;Makimura et al, 2003;Jahng et al, 2005) during food deprivation, and these stress-responding hormones are known to be involved in the arcuate expression of feeding peptides (Tempel and Leibowitz, 1994;Ahima et al, 1996;Zakrzewska et al, 1999;Schwartz et al, 2000;Swart et al, 2002;Makimura et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…mRNA expressions of NPY, proopiomelanocortin (POMC) and cocaine-amphetamine regulated transcript (CART) in the arcuate nucleus responding to food deprivation were examined together with the plasma levels of leptin and corticosterone. Circulating leptin decreases (Schwartz et al, 1995;Ahima et al, 1996;Makimura et al, 2003) and corticosterone increases (Timofeeva et al, 2002;Makimura et al, 2003;Jahng et al, 2005) during food deprivation, and these stress-responding hormones are known to be involved in the arcuate expression of feeding peptides (Tempel and Leibowitz, 1994;Ahima et al, 1996;Zakrzewska et al, 1999;Schwartz et al, 2000;Swart et al, 2002;Makimura et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Glucocorticoids, stress hormones released by activation of the HPA axis, are known to be involved in the regulation of energy balance, 9,10 and some of the central effects of glucocorticoids are believed to be mediated by hypothalamic neuropeptides. 11,12 It has been reported that experiences of repeated MS during pre-weaning period increase the hypothalamic level of neuropeptide Y (NPY) in rats later in life. 13,14 NPY, a potent orexic peptide, stimulates feeding.…”
Section: Introductionmentioning
confidence: 99%
“…LEP and LEPR are known to modulate food intake and energy balance 16 and are responsible for some rare monogenic forms of obesity. 3 When activated, GCCR exerts orexigenic 17 and antithermogenic effects. 18,19 The peripheral sympathetic nervous system is a major player in the regulation of energy balance and the physiological responses to adrenaline and noradrenaline are exerted through the adrenergic receptors a and b.…”
Section: Measurementsmentioning
confidence: 99%